HYDROGEN-RESISTANT PROTECTIVE MATERIALS FOR FRICTION PARTS OF MACHINES AND EQUIPMENT, OPERATING IN TECHNOGENIC HYDROGEN-CONTAINING MEDIA - V. K. Sheleg; A. А. Prisevok (Наука и техника)
The paper contains results of theoretical, methodological and experimental investigations of wearing mechanism, strengthening methods and restoration of friction unit parts operating in contact with bio-chemically-active technogenic hydrogen-containing media. One of the most efficient methods for better wear-resistance of such parts is a formation of protective coatings on their working surfaces using self-fluxing alloys or composite materials on their basis while adding a copper component by gas-thermal spraying. It is established that an addition of a definite quantity of copper leads to formation of multi-component coating of three-layer structure having biocide properties that retard biochemical destruction of a surface coating owing to formed servo-like film that lowers a hydrogen penetration.